2010
DOI: 10.4061/2010/852146
|View full text |Cite
|
Sign up to set email alerts
|

Immunization against Lamb Haemonchosis with a Recombinant Somatic Antigen ofHaemonchus contortus(rHcp26/23)

Abstract: Haemonchosis, caused by the abomasal nematode Haemonchus contortus, is a common parasitic disease of sheep. Our previous results showed that a soluble fraction from adult stages of the nematode (p26/23) induced partial protection against challenge. Recombinant DNA technology was applied to obtain a synthetic protein (rHcp26/23). Immunological assays (ELISA, Western blotting, and immunolocalization), using sera from lambs immunized with p26/23, confirmed the identity of the recombinant protein and demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Identification and development of novel drug targets are always a primacy in the biological study of socio-economically important parasites. Helminths ESPs including some antigens with unknown biological functions were characterized ( 31 33 ), and due to their sequences homology, these molecules have been proven as promising vaccine candidate against nematodes infections ( 34 , 35 ). Among PPs, PP1 elaborate numerous biological activities, such as membrane receptors/channels regulations, protein synthesis, glycogen metabolism, transcription, cellular division, and apoptosis ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Identification and development of novel drug targets are always a primacy in the biological study of socio-economically important parasites. Helminths ESPs including some antigens with unknown biological functions were characterized ( 31 33 ), and due to their sequences homology, these molecules have been proven as promising vaccine candidate against nematodes infections ( 34 , 35 ). Among PPs, PP1 elaborate numerous biological activities, such as membrane receptors/channels regulations, protein synthesis, glycogen metabolism, transcription, cellular division, and apoptosis ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…On contrary, Garcıa-Coiradas et al . [ 14 ] reported that regardless of the strong immune response elicited by the immunization of lambs with the recombinant protein (rHcp26/23) no protection against the H. contortus challenge was found. They recommended numerous explanations behind the lacking denaturalization of the recombinant proteins and glycosylation of the defensive antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Adult male H. contortus was used in an RNA extraction kit protocol (Qiagen, Germany) according to Garcıa-Coiradas et al . [ 14 ]. Reverse transcriptase polymerase chain reaction (PCR) was carried out in two independent steps: Synthesis of cDNA (1 st strand cDNA Synthesis Kit, AMV, Roche) using hexanucleotide random primers with BamHI and HindIII restriction targets:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greatest efficacy has been achieved with vaccines that use irradiated larvae (5), but the logistical problems involved in their production and administration (6) have led to a search for native antigens or recombinant ones (7). The latter are easier to produce and distribute, and many of them are proteases, cysteine proteases, metalloproteases, aspartyl proteases (PEPs), all proteins from the helminth intestine, and some with unknown biological functions (8)(9)(10)(11). Due to the homology in their sequences, some of these antigens have proved to be effective against different nematode species (3,12,13).…”
mentioning
confidence: 99%